The cultural industries in the digital era - Pineda de Alcázar, Migdalia (2008)
This article, that comprises of a work ofinvestigation in course, titleholder "Society of the Informacion, massive culture and mass media", touches to the subjetc of the changes undergone by the cultural industries from the convergence of classic mass media with the technologies of the information and the communication. Also it makes reference toche new forms of consumption and cultural participation of the citizens by means of the digital networks, finally to propose some indispensable actions in the definition of Cultural Policies that allow a balance between the intereses of the globalised cultural industries and the rights of the civil society.